1962
DOI: 10.1128/jb.83.3.616-623.1962
|View full text |Cite
|
Sign up to set email alerts
|

GENETIC INSTABILITY WITH EPISOME-MEDIATED TRANSFER IN ESCHERICHIA COLI

Abstract: Gundersen, Wenche B. (Oslo University, Oslo. Norway), Kaare Jyssum, and Sverre Lie . Genetic instability with episome-mediated transfer in Escherichia coli . J. Bacteriol. 83: 616–623. 1962.—Hospital strains of Escherichia coli have been simultaneously screened for an increased mutation rate to streptomycin (Sm) resistance and to auxotrophy. Two strains were found with an increased mutation rate to Sm, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

1965
1965
1973
1973

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 19 publications
1
18
0
Order By: Relevance
“…It is, howeve r, ex pressed befo re th e fir st cell di vis ion, su gges tin g it is n ot recessive ( 10 ). Th e p a rti cul a r streptomycin res is ta n ce of th e celt s ca rryin g th e mutato r fac tor in its ex tra chrom osom a l s tat e will protect th e cell s aga in s t quite high concentrations of s tre ptom ycin, at leas t 200 llg per ml when th ey are grow in g in minim a l m edium ( 4). Ther e is reason to beli eve th a t th e appa rent need for phenomic lag when selec ting for reco mbinants with 100 llg of s trep tom ycin per ml, as was done in th e expe rim ents lis ted in T abl e 1, is not a n actual phenomic lag a llowin g tim e for integ ration a nd seg rega tion of a gen e ti c mark e r, but rather a chan ge in the physiologi cal condition of the cell s. S U ~I r.J A R Y Tran sdu c tion t echniqu e h as b ee n appli ed as a n a ttempt to further elu cid a te th e ge n eti c n a ture of th e s trep tom yc in resistanc e resulting fro m th e ac tion of th e muta tor factor in E .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is, howeve r, ex pressed befo re th e fir st cell di vis ion, su gges tin g it is n ot recessive ( 10 ). Th e p a rti cul a r streptomycin res is ta n ce of th e celt s ca rryin g th e mutato r fac tor in its ex tra chrom osom a l s tat e will protect th e cell s aga in s t quite high concentrations of s tre ptom ycin, at leas t 200 llg per ml when th ey are grow in g in minim a l m edium ( 4). Ther e is reason to beli eve th a t th e appa rent need for phenomic lag when selec ting for reco mbinants with 100 llg of s trep tom ycin per ml, as was done in th e expe rim ents lis ted in T abl e 1, is not a n actual phenomic lag a llowin g tim e for integ ration a nd seg rega tion of a gen e ti c mark e r, but rather a chan ge in the physiologi cal condition of the cell s. S U ~I r.J A R Y Tran sdu c tion t echniqu e h as b ee n appli ed as a n a ttempt to further elu cid a te th e ge n eti c n a ture of th e s trep tom yc in resistanc e resulting fro m th e ac tion of th e muta tor factor in E .…”
Section: Discussionmentioning
confidence: 99%
“…Thu s the fact was revealed that th e presence of the mutator fac tor in its extrachromosomal st a le protects the cell s against the lethal eff ect of s trep tom ycin und e r certa in conditions. Th e r esults from inves ti gation of this problem are reported elsewhere (4) . The present experim ents show that it is possible to transfer th e mutator factor from a mutator or a mutator-streptomycinresistant cell to a mutator-nega tive cell by m ea ns of tran sd ucing phage as well as by infection.…”
Section: Examination Of the Str Ep Lomycin Character Of Th E R Eco Mmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacterial strains. The strain used for the preparation of E. coli ISN extract was E. coli K12 T71 (10). The mutants of N .…”
Section: A T E R I a L S A N D M E T H O D Smentioning
confidence: 99%
“…It will be noted that the technique u sed in this expe rim ent is analogous with th a t used in genetic cross in th e E. co li K 12 sys tem (8) . In th e enterobacterium th e conjugation takes p lace within a period m easured in minutes, and th e tim e-fac tor may be s tudi ed by m ea n s of interrupted mating.…”
Section: Gen Etic R Ecombination Betwee N Arzxolrophsmentioning
confidence: 99%